GO–NGO Teamwork for Strengthening Local Governance: A Review of Extant Literature in the Context of Bangladesh. (March 2022) - Mojumder, Mohammad Jahangir Hossain; Panday, Pranab Kumar
Local governance has come into the centre of discourses after phenomenal shifts in functions, roles, and governing process of the central government. The increasing burden of the central government due to multidimensional challenges of modernisation and globalisation has necessitated the strengthening of local government organisations (GOs) through decentralisation of power. However, in most cases, the central government has retained the power to control local government. Factors such as central control, lack of capacity of the local government officials and lack of finances have made local government organisation of developing countries, including Bangladesh, non-functional. Therefore, many development organisations and donors have come forward with different assistances for strengthening these bodies. This article presents a review of an extant literate of GO–NGO teamwork for strengthening local government. The review finds that network among the central government, NGOs and local government could strengthen local governments in Bangladesh to effectively discharge its responsibilities.